The Borrowing Process of English Loanwords on Covid-19 in Indonesian - Nurul Chojimah; Estu Widodo (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
AbstractThis research was aimed at finding out the patterns of English loans on Covid-19 into Indonesian and their borrowing processes. Data for this qualitative study were English borrowing words and phrases functioning to denote Covid-19 issues which are massively used by Indonesians. The data were obtained from various sources such as mass media, official documents, notices in public places, daily conversation, and others. The classification of borrowing by Haugen (1950) was used in this study. Data analysis was done by comparing the original forms of the loanwords and the phonologically-and-morphologically ‘imitated’ ones. Findings of this study reveal that English loans on Covid-19 can be classified into loanwords, loanblends, and loanshift, each of which has its own borrowing processes. None-phonemic substitution, partial-phonemic substitution, and total phonemic substitution are the borrowing process of loanwords. Spelling adjustment and letter omission are the borrowing methods of loanblends. Loan translation is the only borrowing process for loanshift. This study recommends that future research use more data on health realm in order to make a more comprehensive description of the borrowing process in Indonesian. Keywords: borrowing process; covid-19, loanblend; loanshift; loanword.